Periodontite apical em pacientes em hemodiálise e sua correlação com parâmetros nutricionais e inflamatórios sistêmicos - Argenta, Laércio Cassol (2019)
Introduction: Inflammatory processes in patients undergoing renal replacement therapy are frequent, multifactorial and associated with cardiovascular events, malnutrition and anemia, all correlated with mortality in this population. Odontogenic foci are a potential cause of systemic inflammation and poorly investigated in these patients. This study aimed to evaluate the presence of apical periodontitis (AP) in hemodialysis patients, its correlation with systemic and nutritional inflammatory markers, and the use of neutrophils and platelets with lymphocytes (NLR and PLR) as inflammatory markers (IM). The study was divided into three articles: 1 - Evaluation of the prevalence and distribution of AP and its characteristics in hemodialysis patients; 2 - Correlations between NLR and PLR with high-sensitivity C-reactive protein (hsCRP), albumin and hsCRP/albumin ratio among them and with clinical variables of patients on hemodialysis; 3 - Correlation between periapical lesions and systemic inflammatory markers. Methodology: Study 1 – A sample of 116 hemodialysis patients, 54% male, 30% diabetic, with mean age of 50 years and mean time of dialysis therapy of 58 months, were evaluated with periapical radiography. Were evaluated teeth with and without endodontic treatment (ET), which were divided into adequate or inadequate. The Orstevik index was used to classify periapical lesions. Study 2 - The correlations between NLR and PLR with hsCRP, hsCRP/albumin ratio and albumin between them and those with clinical variables were measured in 242 patients on hemodialysis. Study 3 - The patients were divided into two groups (with and without AP) and evaluated for differences between groups in relation to inflammatory markers and clinical variables. In the group with lesions, a correlation analysis was performed with the inflammatory markers and clinical variables. Results: Study 1 - A prevalence of AP was found in 7.2% of a total of 2245 teeth examined, with AP in 55% of patients. Endodontic treatment was found in 2.85% of the teeth, with 84.4% of these considered inadequate, of which 57% had periapical lesion. Study 2 – The NLR and PLR showed a positive correlation with hsCRP and hsCRP/albumin, and negative correlation with albumin. The PLR correlated positively with resistance to erythropoietin and negatively with hemoglobin. The NLR correlated positively with time on dialysis, and hsCRP and hsCRP/albumin correlated negatively with the ureic nitrogen apearance rate. Study 3 – The groups with and without AP and lesions evaluated by the PAI index did not show significant correlations with the IM: NLR, PLR, hsCRP and CRP/albumin. Patients with AP were older (p = 0.02). Conclusions: Study 1 - Chronic AP are frequent in patients on hemodialysis, consisting in potential inflammatory foci to be treated. Study 2 – The NLR and PLR correlated positively with hsCRP and hsCRP/albumin, consisting of an easy method and at no additional cost to monitor systemic inflammation. Study 3- The NLR, PLR and hsCRP were not useful in discriminating patients with or without AP, and their elevations may be due to other causes and/or radiologically detected dental alterations do not present systemic repercussions manifested through these markers.